Update: factors influencing heart rate variability - a narrative review - Sammito, S.; Thielmann, B.; Böckelmann, I. (Frontiers in Physiology, 2024)
Objective: Heart rate variability (HRV) is an important non-invasive marker for the assessment of an organism`s autonomic physiological regulatory pathways. Lower HRV has been shown to correlate with increased mortality. HRV is influenced by various factors or diseases. The aim of this narrative review is to describe the current state of knowledge on factors influencing HRV and their significance for interpretation.